Endoscopic Management of Symptomatic Duodenal Duplication Cysts: Two Case Reports - Campos,Sara Teles de (2022)
Abstract Background: Duodenal duplication cysts (DDCs) are rare congenital anomalies typically manifesting during childhood. Clinical manifestations are uncommon in adulthood. DDCs were classically treated surgically, but endoscopic treatment has been increasingly reported. Endoscopic cyst marsupialization establishes a communication between the cyst cavity and the duodenal lumen so that the cystic content can be drained continuously into the duodenum. We herein describe two cases of symptomatic DDCs diagnosed in adulthood and submitted to endoscopic marsupialization using different techniques and devices. Case Summary: Case 1: A 23-year-old female patient was admitted with the diagnosis of acute pancreatitis. Endoscopic ultrasound revealed a 35-mm duodenal subepithelial lesion whose proximal limit was immediately distal to the ampulla of Vater and filled with fluid and calcifications. Using a duodenoscope, deroofing of the lesion was made with a diathermic snare. Pathology confirmed the diagnosis of DDC. Case 2: A 41-year-old female, submitted to laparoscopic cholecystectomy 1 month earlier due to suspected lithiasic acute pancreatitis, was admitted due to suspicion of iatrogenic biliary fistula. An endoscopic retrograde cholangiopancreatography was performed and the bile leak was treated. Immediately distal to the papillary orifice, a 20-mm subepithelial lesion was also detected. A biopsy forceps was used to fenestrate its wall, allowing the exit of mucous fluid and stones, and a sphincterotome was used to expand the incision. No recurrence was documented in both cases. Conclusion: These cases highlight DDC as a potential cause for acute pancreatitis in adults and endoscopy as an easy treatment option.